Respuesta :

The equation that has the same solution as x² + 8x + 15 = -4x is x = -6± √21.

How do you solve the above equation?

Step 1 - Move terms to the left

x² + 8x + 15 = -4x

x² + 8x + 15-(-4x) = 0

Step 2  - Combine the terms

x² + 8x + 15 + 4x = 0

x² + 12x + 15 = 0

Step 3 - Apply the quadratic formula

x = (-b ± √(b² - 4ac) )/ 2a

Recall that form our equation:

a = 1

b = 12

c = 15

Thus,  x = (-12 √(12² - 4 * 1 *15) )/2 *1

x = -6 ± √21


Learn more about equations at:
https://brainly.com/question/2972832
#SPJ1